Structure of neuroendocrine regulatory peptide‐2 in membrane‐mimicking environments. Issue 3 (19th October 2020) - Park, One‐Sung; Bang, Jeong Kyu; Ryu, Kyoung‐Seok; Hwang, Eunha; Hong, Kwan Soo; Byun, Youngjoo; Cheong, Chaejoon; Jeon, Young Ho
Abstract: Neuroendocrine regulatory peptide‐2 (NERP‐2) is involved in the maintenance of homeostasis and regulates various metabolic activities. NERP‐2 is derived from the VGF neuropeptide precursor, which is induced by various neurotrophins. Despite increasing interest in the functions of NERP‐2, the structure of this peptide has not been reported. In this study, the structure of the NERP‐2 peptide was investigated using circular dichroism and nuclear magnetic resonance (NMR) spectroscopy. NERP‐2 exists as a partial helical structure in buffer solutions, and the helical structure exhibits more stable behaviors in hexafluoroisopropanol (HFIP) or dodecylphosphocholine (DPC) micelle. We determined its 3D structure in both HFIP and DPC micelle solutions using NMR spectroscopy. NERP‐2 adopted a predominantly helical structure in HFIP solutions, while only the central portion of the protein was helical in the DPC solutions. The amphipathic nature of helical structure implies the potential structural changes in NERP‐2 upon receptor binding. Abstract :